Commutativity and spectral properties of genuine Baskakov-Durrmeyer type operators and their \(k\)th order Kantorovich modification - Margareta Heilmann (Journal of Numerical Analysis and Approximation Theory, 2015)
In this paper we present an overview of commutativity results and different methods for the proofs for  Baskakov-Durrmeyer type operators and associated differential operators. We discuss the spectral properties and generalize all results to \(k\)th order Kantorovich modifications and corresponding Durrmeyer type variants of Bleimann, Butzer and Hahn operators and Meyer-Konig and Zeller operators.